2021
DOI: 10.1021/acs.orglett.1c01723
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Aryl Thio/Selenoglycosides via the Catellani Strategy

Abstract: We described a novel palladium-catalyzed domino procedure for the preparation of (hetero)­aryl thio/selenoglycosides. Readily available (hetero)­aryl iodides and easily accessible 1-thiosugars/1-selenosugars are utilized as the substrates. Meanwhile, 10 types of sugars are quite compatible with this reaction with good regio- and stereoselectivity, high efficiency, and broad applicability (up to 89%, 53 examples). This method enables the straightforward formation of the C­(sp2)–S/Se bond of (hetero)­aryl thio/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Also, Messaoudi and co-workers established a PdG3 XantPhos-catalyzed coupling reaction of an in situ generated anomeric selenolate anion from β- p -methylbenzoyl selenoglycoside with aryl/alkenyl iodides for synthesizing selenoglycosides (Scheme b). In 2021, the Liang group first developed palladium/norbornene cooperative catalyzed ortho -acylation and ipso -thio/selenolation for the synthesis of aryl S/Se-glycosides via the Catellani Strategy (Scheme c). The green process involving both the glycosylthio/seleno group and acyl group to incorporate into another moiety in an atom economical manner to avoid the generation of waste has remained elusive .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Messaoudi and co-workers established a PdG3 XantPhos-catalyzed coupling reaction of an in situ generated anomeric selenolate anion from β- p -methylbenzoyl selenoglycoside with aryl/alkenyl iodides for synthesizing selenoglycosides (Scheme b). In 2021, the Liang group first developed palladium/norbornene cooperative catalyzed ortho -acylation and ipso -thio/selenolation for the synthesis of aryl S/Se-glycosides via the Catellani Strategy (Scheme c). The green process involving both the glycosylthio/seleno group and acyl group to incorporate into another moiety in an atom economical manner to avoid the generation of waste has remained elusive .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, the Liang group first developed palladium/norbornene cooperative catalyzed ortho -acylation and ipso -thio/selenolation for the synthesis of aryl S/Se-glycosides via the Catellani Strategy (Scheme c). The green process involving both the glycosylthio/seleno group and acyl group to incorporate into another moiety in an atom economical manner to avoid the generation of waste has remained elusive . However, the cross-coupling protocol or Modular synthesis approach demands reaction conditions such as high catalyst loadings (30 mol % in the case of Ni catalysis), specialized phosphine ligands for the Pd catalysis, elevated reaction temperatures (80–120 °C cases of Pd or Cu catalysis), and long reaction times which often limit the practicability or the scope of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, NaOH and KO t Bu provided only 10-15 % of yield in water solvent under standard condition (Table 1, entry 10-12). Standardizing temperature revealed that there is no product formation below 70 °C in water solvent (Table 1, entry [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalyzed transformation of thioesters via C(O)–S bond cleavage is a promising synthetic route to construct C–C and C–heteroatom bonds (Scheme 1a). 12 Thioesters have also been used as bifunctional agents in Pd-, Pt-, and Rh-catalyzed thioacylation or decarbonylative carbothiolation of alkynes, 13 allene, 14 diazos, 15 aryl halides, 16 and 2-naphthylamine. 17 The difunctionalization of alkenes with thioesters remains largely unexplored (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%